Analysis of Using Behavior on the GoHalalGo Application: UTAUT Model Approach - Ramli , Aisyah Alizza Rahmah; Safaria, Siti; Rizki, Muhammad Nur (Formosa Journal of Sustainable Research, 2024)
The main objective of this research is to examine how performance expectations, social influences, effort expectations, and facilitating conditions impact user behavior on the GoHalalGo halal travel application in Indonesia. The research used a quantitative survey method, sampling was carried out randomly on 253 GoHalalGo users. This research uses Partial Least Squares (PLS) analysis to test the hypothesis. Findings from the SmartPLS analysis show that performance expectations, social influence and effort expectations are highly influential factors on behavioral intention. Facilitating condition has no significant effect on behavioral intention, however facilitating condition has a significant effect on using behavior. Furthermore, these factors have a significant influence on user intentions in using the GoHalalGo application